Suicides and attempted suicides in alcohol and other substance use disorders - Bakım, Bahadır; Karamustafalıoğlu, K. Oğuz; Akpınar, Abdullah (Journal of Dependence, 2007)
Objective: Alcohol and substance use increases, while the age of onset of alcohol and substance use keeps dropping, which is important for our country because of its young population. Suicides and attempted suicides related to substance and alcohol use and comorbidity may be prevented by effective treatment. Our aim is to determine the factors which increase suicide risk and review treatment options for this problem. Method: We searched PubMed search engine, Tübitak Türk Tıp Dizini, Çukurova Psikiyatri Dizini and ULAKBİM Catalogue in order to find related literature published between 1988-2006 years with keywords “suicide, alcohol and drug abuse-dependence, psychiatric comorbidity” Results: Subtance and alcohol abusers have an elevated risk of suicide and attempted suicide. Major depressive disorder and bipolar disorder patients who attempt suicide frequently have comorbide alcohol and/or substance abuse disorder and various personality disorders. A significant proportion of those patients who commit or attempt suicide are substance abusers and/or intoxicated (by alcohol) at the time of the event. Substance abuse may enhance vulnerability through depression and social disintegration. Intoxication may trigger suicidal impulses in vulnerable individuals. Psychiatric comorbidity is a significant risk factor for both completed and attempted suicide among both alcohol and drug abusers. Conclusion: Genetic predisposition, history of suicide attempts, hospitalization of high risk patients, diagnosis and treatment of psychiatric comorbidities are important. Developing strategies for treatment of high risk patients may help in decreasing suicide deaths.